Étude épidémiologique et moléculaire de la leishmaniose cutanée dans les régions de Souss-Massa et Drâa-Tafilalet - EL ALEM Mohamed Mahmoud Ould Mohamed (Faculté des Sciences de Rabat, 2021)
The main objectives of this study are to characterize the causative agents of cutaneous leishmaniasis (CL) and to determine the risk factors of contracting this disease in the regions of Souss-Massa and Drâa-Tafilalet, based on the spatial distribution of CL cases related to environmental factors and other factors such as socio-economic and demographic factors. The results showed that among all the variables introduced in the study, socioeconomic status and rainfall are the strongest predictors associated with the number of CL cases. Molecular identification of the causative agent of CL, by PCR-ITS1-RFLP, revealed the presence of three species of Leishmania (L. major, L. tropica and L. infantum) in these regions. Our study allowed, on the one hand, the updating of epidemiological data of the LC in the regions of Souss-Massa and Drâa-Tafilalt and on the other hand, the updating of the distribution of Leishmania species in these regions, which will make it possible to better orient the strategies control this parasite and to reduce the prevalence of CL.
Epidemiological and molecular study of cutaneous leishmaniasis in the regions of Souss-Massa and Drâa-Tafilalet
Keywords: Biologie; Biologie